Ranolazine-Mediated Attenuation of Mechanoelectric Feedback in Atrial Myocyte Monolayers - Del-Canto, Irene; Gómez-Cid, Lidia; Hernández-Romero, Ismael; Guillem, María S.; Fernández-Santos, María Eugenia; Atienza, Felipe; Such, Luis; Fernández-Avilés, Francisco; Chorro, Francisco J.; Climent, Andreu M. (Frontiers in Physiology, 2020)
Mechanical stretch increases Na+ inflow into myocytes, related to mechanisms including stretch-activated channels or Na+/H+ exchanger activation, involving Ca2+ increase that leads to changes in electrophysiological properties favoring arrhythmia induction. Ranolazine is an antianginal drug with confirmed beneficial effects against cardiac arrhythmias associated to the augmentation of INaL current and Ca2+ overload. This study investigates the effects of mechanical stretch on activation patterns in atrial cell monolayers and its pharmacological response to ranolazine. Confluent HL-1 cells were cultured in silicone membrane plates and were stretched to 110% of original length. The characteristics of in vitro fibrillation (dominant frequency, regularity index, density of phase singularities, rotor meandering and rotor curvature) were analyzed using optical mapping in order to study the mechanoelectric response to stretch under control conditions and ranolazine action. HL-1 cell stretch increased fibrillatory dominant frequency (3.65±0.69 vs. 4.35±0.74 Hz, p<0.01) and activation complexity (1.97±0.45 vs. 2.66±0.58 PS/cm2, p<0.01) under control conditions. These effects were related to stretch-induced changes affecting the reentrant patterns, comprising a decrease in rotor meandering (0.72±0.12 vs. 0.62±0.12 cm/s, p<0.001) and an increase in wavefront curvature (4.90±0.42 vs 5.68±0.40 rad/cm, p<0.001). Ranolazine reduced stretch-induced effects, attenuating the activation rate increment (12.8% vs. 19.7%, p<0.01) and maintaining activation complexity - both parameters being lower during stretch than under control conditions. Moreover, under baseline conditions, ranolazine slowed and regularized the activation patterns (3.04±0.61 vs. 3.65±0.69 Hz, p<0.01). Ranolazine attenuates the modifications of activation patterns induced by mechanical stretch in atrial myocyte monolayers.